Comparative study on reproductive biology of Ompok hypopthalmus from the Kampar Kiri and Kampar Kanan Rivers, Kampar Regency, Riau Province - Betsyeba Yunita Siregar; Windarti Windarti; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Comparative study of reproductive biology Ompok hypopthalmus from the Kampar Kiri and Kampar Kanan Rivers has been conducted on April-May 2018. As there are differences on water condition and water quality in the Kampar Kiri and Kampar Kanan Rivers, the biological aspects of the reproductive of O. hypopthalmus living in those areas might be different. Sixty one fishes (28 males and 33 females) were taken from the Kampar Kiri River and 54 fishes (29 males and 25 females) were collected from the Kampar Kanan River. Total length of the fishes captured in the Kampar Kiri River was 150-220 mm (males) and 158-235 mm (females), while those of the Kampar Kanan River were 132-242 mm (males) and 145-226 mm (females). Sex ratio of fishes in the Kampar Kiri was 1:1.2 and that of the Kampar Kanan was 1:1. All fishes captured shown trace of developing gonads. In all maturity levels, the GSI of fish from the Kampar Kiri River was higher than that of the Kampar Kanan River, they were 0.27-5.95% in the Kampar Kiri’s fishes and 0.84-5.43% in the Kampar Kanan’s fishes. The fecundity of the Kampar Kiri’s fishes also higher than that of the Kampar Kanan’s fishes, they were 2.488-14.927 eggs/fish in the Kampar Kiri’s fishes and 4.858-8.106 eggs/fish in the Kampar Kanan’s fishes. Egg diameter in the Kampar Kiri and Kampar Kanan River were similar, 0.70-1.50 mm. Based on data obtained, it can be concluded that the reproductive biology of the Kampar Kanan’s fishes was worse than that of the Kampar Kiri’s fishes.Keyword: Sex Ratio, Gonad Maturity Level, Gonad Somatic Index, Fecundity